OPTIMALISASI KINERJA KARYAWAN PERUSAHAAN CATERING : PERSPEKTIF TEORI KEPEMIMPINAN ISLAMI DAN KESEJAHTERAAN - Bulan, Clarissa Chandra (Universitas Semarang, 2025)
This study aims to explore the factors influencing employee performance at CV Berkah Catering, a catering company in Semarang, Indonesia. The study analyzes the role of Islamic leadership, employee welfare, training, internal communication, and compensation and incentives in improving employee performance. The results indicate that leadership based on Islamic values emphasizing trustworthiness, justice, and ihsan has a positive impact on employee motivation and engagement. Furthermore, employee well-being, encompassing physical, mental, and spiritual aspects, contributes to increased productivity and job satisfaction. More comprehensive training, more efficient internal communication, and a fair compensation system can improve team dynamics and enhance company performance. The study concludes that implementing Islamic principles in employee management can sustainably improve performance in the catering sector.